EPISTEMOLOGICAL QUESTIONS FOR A PSYCHOLOGY OF DIALOGUE - BAKER, Michael J. (Studia Universitatis Babeș-Bolyai Philosophia, 2022)
Notwithstanding the magisterial work of the psychologists H. H. Clark and A. Trognon , in comparison with sociology and linguistics a veritable psychology of dialogue still remains little elaborated. This paper analyses epistemological obstacles facing such an enterprise, arguing that dialogue cannot be understood as a window on the individual mind. A vision of dialogue as a process of collective thinking, with the exchange as the fundamental unit of analysis, is sketched out. Dialogue is a complex system, involving multidirectional relations between situational representations, communicative action and emergent thinking.